Identifying the Effect of Harm on Competition in Price Parity Agreements - Sih Yuliana Wahyuningtyas (Universitas Katolik Indonesia Atma Jaya, 2022)
The paper aims to examine the harmful elements of price parity agreements by expounding showcases from Indonesia and Germany and discussing whether the rule of reason is the best approach to prohibit price parity agreements. The research is based on a normative legal study using legal comparison (Indonesia, Germany, and the European Union); the data is collected employing library research. The harmful elements of price parity agreements lie in limiting the freedom of suppliers to set prices and creating entry barriers for new players. The rule of reason approach to defining illegality is based on assessing the harmful effects of conduct, which implies that the respective conduct as such (per se) is not prohibited and becomes prohibited only when the second part of the clause is met. Further, although an effect assessment is required, the approach does not require an actual effect. A potential effect is sufficient for the prohibition. The originality of the paper is found in three aspects: first, the analysis of legal theories and regulations by challenging them with a different approach from the current approach for competition law assessment; second, drawing conceptual solutions to deal with the current problems; and third, providing scientific arguments to underpin the use of the application approach.